"The Necessary Ornaments of Place": Similarity and Alterity in the Persianate Imaginary. (19th June 2019) - Kia, Mana
Abstract : This article analyzes representations of place in seventeenth-century texts to consider how early modern Persians made sense of the world. The Persian formulation of alterity stands in contrast to Edward Said's formulation about Orientalism, by which Europe makes itself into the West. In early modern Persianate Asia, common representations of place appear in geographical and travel writing. These shared features, which I call ornaments, adorned both places that shared a learned Persian language, Muslim rule, and those beyond, in other parts of Asia and Africa. The presence or absence of these ornaments made the world intelligible for early modern Persians, creating categories of similarity and alterity that were partial, diffuse, and aporetic, defying the self-other distinctions of Orientalism. This form of knowledge about the self and the world then generated the possibility for encounters different from both modern colonial power and the nation-state.